2002
DOI: 10.1021/np010039x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Natural Products from Curcuma longa that Protect Cells from Beta-Amyloid Insult:  A Drug Discovery Effort against Alzheimer's Disease

Abstract: From Curcuma longa, two novel compounds, 4' '-(3' "-methoxy-4' "-hydroxyphenyl)-2' '-oxo-3' '-enebutanyl 3-(3'-methoxy-4'hydroxyphenyl)propenoate (calebin-A, 1) and 1,7-bis(4-hydroxy-3-methoxyphenyl)-1,4,6-heptatrien-3-one (2), and seven known compounds, 1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione (curcumin, 3), 1-(4-hydroxy-3-methoxyphenyl)-7-(4-hydroxyphenyl)-1,6-heptadiene-3,5-dione (demethoxycurcumin, 4), 1,7-bis(4-hydroxyphenyl)-1,6-heptadiene-3,5-dione (bisdemethoxycurcumin, 5), 1-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(165 citation statements)
references
References 40 publications
3
157
0
2
Order By: Relevance
“…In vitro studies have shown that curcumin can retard the process of amyloid ␤ (A␤) aggregation (5,6), which is supposed to be the initiator of AD. It disrupts the formation of the long straight A␤ fibrils (5,7) and reduces A␤ toxicity (8,9). Moreover, it can also disrupt the preformed A␤ fibrils (6,7).…”
Section: ؉mentioning
confidence: 99%
“…In vitro studies have shown that curcumin can retard the process of amyloid ␤ (A␤) aggregation (5,6), which is supposed to be the initiator of AD. It disrupts the formation of the long straight A␤ fibrils (5,7) and reduces A␤ toxicity (8,9). Moreover, it can also disrupt the preformed A␤ fibrils (6,7).…”
Section: ؉mentioning
confidence: 99%
“…The protection of PC12 cells from Aβ by chlorogenic acid was determined by measuring the potential of the cell to reduce MTT to MTT formazan, which indicates the cell viability (Park and Kim, 2002). Briefl y, exponentially growing PC12 cells (4×10 4 cells/well) were plated in 96-well tissue culture plates, after which the cells were pretreated with different concentrations of chlorogenic acid (1, 4, 20 and 100 μg/ml) for 1 h. As a vehicle control, cells were treated with 0.1% DMSO.…”
Section: Determination Of the Ability Of Chlorogenic Acid To Protect mentioning
confidence: 99%
“…The common use of tumeric as a curry spice has pointed to its main constituent, curcumin, as a possible mediator of anti-Ab effects. Indeed, curcumin and related compounds like calebin-A, dimethoxycurcumin, and bidemethoxycurcumin, inhibit fibril formation and extension and promote destabilization of pre-aggregated Ab peptides [Kim et al, 2005;Ono et al, 2004;Park and Kim, 2002;Yang et al, 2005]. Examination of the structure-activity function of curcumin has identified three important molecular features, including a hydroxyl substitution on the aromatic end group, a narrow linker length between 8-16 Å , and the presence of a second terminal phenyl group that determines its anti-aggregant properties [Reinke and Gestwicki, 2007].…”
Section: Curcuminmentioning
confidence: 99%
“…Examination of the structure-activity function of curcumin has identified three important molecular features, including a hydroxyl substitution on the aromatic end group, a narrow linker length between 8-16 Å , and the presence of a second terminal phenyl group that determines its anti-aggregant properties [Reinke and Gestwicki, 2007]. In vitro, curcumin protects against Ab-induced death of PC-12, SH-SY5Y neuroblastoma, and human umbilical vein endothelial cells, via anti-oxidant actions [Baum and Ng, 2004;Kim et al, 2001;Park and Kim, 2002;Yang et al, 2005]. Not surprisingly, intravenously-injected curcumin binds to parenchymal and vascular amyloid deposits in the brains of TgAPP swe / PS1 and Tg2576 mice [Garcia-Alloza et al, 2007;Yang et al, 2005].…”
Section: Curcuminmentioning
confidence: 99%